Biostratigraphy and taxonomy of late Albian planktonic foraminifera from ODP Leg 171B (western North Atlantic Ocean) - M.R. PETRIZZO; B. T. HUBER (The Journal of Foraminiferal Research, 2006)
A detailed taxonomic and biostratigraphic analysis of upper Albian planktonic foraminifera is presented for Ocean Drilling Program sites 1050 and 1052, which were deposited at similar to 23 degrees N paleolatitude and similar to 1300 m and 300 m paleodepths, respectively, on the Blake Nose escarpment (subtropical western North Atlantic Ocean). The generally excellent preservation of the material, especially in the clay-rich layers, permits recognition of new bioevents within the uppermost Albian, in addition to most of the standard bioevents that have been previously defined in the Tethyan Realm. The taxonomic assignments and the stratigraphic range of some species that are often overlooked or misidentified in the stratigraphic record have also been clarified, and three species are formally described as new (Hedbergella astrepta, H. praelibyca and H. blakensis). Graphic correlation and age-depth curves constructed from integrated planktonic foraminifera and calcareous nannofossils datum events enable reliable estimation of the relative timing of species first and last occurrences and relative abundance variations, as well as determination of the timing and extent of an unconformity at Site 1050. While most of the species datum events are well correlated, several are found to be diachronous and/or unreliable probably as a result of different surface water conditions along the depth transect.